Metal-free base-mediated oxidative annulation cascades to 3-substituted-3-hydroxyoxindole and its 3-spirocyclic derivative - Liu, Min; Zhang, Chunxia; Ding, Mingruo; Tang, Bencan; Zhang, Fengzhi (The Royal Society of Chemistry, 2017)
A simple and efficient method was developed for the construction of the medicinally important 3-substituted-3-hydroxyoxindoleand its 3-spirocyclic derivativeswith readily available aniline derivatives as starting materials. Thishighly atom-and step-economical one-pot protocolwas carried out undermetal-freebase-mediated conditions througha novel oxidative annulationstrategywith oxygen as the oxidant.The key intermediates were isolated and confirmed.A reasonablereaction pathway was proposed and supported by both the preliminary experiments and computational studies.